Bekenntnisse der Hochstaplers Felix Krull: Der Memoiren erster Teil - Mann, Thomas 1875-1955 (Frankfurt am Main Fischer, 1989)
The novel is narrated by the protagonist, an impostor and adventurer named Felix Krull, the son of a ruined Rhineland winemaker. Felix avoids military service and makes his way to France, where he takes a job in a prestigious hotel, first as an elevator operator, then as a waiter. Deftly using his natural charm, good looks, and subtle intelligence, the young man easily wins the heart of a rich writer, as well as part of her money. Later, Krull meets the young Marquis de Venosta and undertakes to help him in his love affairs; he substitutes for the Marquis on a trip around the world.
Paul Thomas Mann (1875-1955) was a German novelist, short story writer, social critic, philanthropist, essayist, and the 1929 Nobel Prize in Literature laureate. His highly symbolic and ironic epic novels and novellas are noted for their insight into the psychology of the artist and the intellectual.
'Bekenntnisse des Hochstaplers Felix Krull' is an unfinished novel, first published in 1954. The novel is a parody of Goethe's autobiography Poetry and Truth, particularly in its pompous tone.
Keywords: 20th Century (1901-2000); Literature; Novel